Decreased levels of regulatory B cells in patients with systemic sclerosis: association with autoantibody production and disease activity - Matsushita, Takashi; Hamaguchi, Yasuhito; Hasegawa, Minoru; Takehara, Kazuhiko; Fujimoto, Manabu (Rheumatology (Oxford, England), 2016)
B cell abnormalities characterized by autoantibody production and polyclonal B cell activation play an important role in the pathogenesis of SSc. IL-10 producing regulatory B (Breg) cells also play an important role in the negative immune response. We identified a human Breg cell subset that was predominantly found within the CD24(hi)CD27(+) B cell subpopulation. However, the role of Breg cells in SSc remains unknown. The aim of this study was to investigate the clinical association of Breg cells in SSc patients. Blood IL-10 producing Breg cell levels were determined by FACS in 35 SSc patients and 30 healthy subjects. In a follow-up study, we analysed six individual dcSSc patients before and after treatment. The frequency of blood Breg cells was significantly lower in SSc patients than in healthy controls (P < 0.0001). Similarly, the frequency of CD24(hi)CD27(+) B cells was significantly lower in SSc patients than in healthy controls (P < 0.0001). SSc patients with decreased Breg cell levels often had interstitial lung disease (P < 0.05). Furthermore, Breg cell levels correlated negatively with the titre of anti-topo I antibody (Ab) and anticentromere Ab in SSc patients. For a follow-up study, Breg cell levels in dcSSc patients after treatment were found to be significantly increased compared with those before treatment (P < 0.05), accompanied by decreased disease activity. Thus, Breg cell levels were inversely correlated with disease activity of SSc. These results suggest that decreased Breg cell levels may contribute to the development of SSc.